On-line speciation and quantification of four arsenical species in rice samples collected in Argentina using a HPLC-HG-AFS coupling - Farías, Silvia S. (2015)
An investigation was carried out to explore further the analytical capabilities of the coupling high performance liquid chromatography (HPLC)-hydride generation (HG)-atomic fluorescence spectrometry (AFS) for the reliable determination of the four toxicologically relevant arsenical species namely, As(III), As(V), monomethylarsonic acid (MMA) and dimethylarsinic acid (DMA) in rice. Fifty nine samples of rice of five different cultivars were collected in province of Entre Rios (Argentina). Samples were dried at 103±2°C and mild conditions were adopted for species extraction (0.28molL-1 HNO3 at 95±3°C for 90min). Method validation included, evaluation of linearity; limits of detection, 0.020μgg-1 for As(III) and 0.025μgg-1 for the other three species; precision (intermediate precision), 4% for As(III) and DMA, and 6% for the other two species; trueness (bias), 9% for As(III) and As(V) and 11% for the other two species, and uncertainty (obtained from validation data) varying from 9.5% for As(III) to 19% for As(V). Total arsenic concentrations ranged from 0.08 to 1.39mgkg-1. The mean concentrations of sum of the As species extracted and determined by HPLC-HG-AFS was approximately 99.7% of certified value for total As in NIST SRM "Rice flour". Levels of the four species in the analyzed samples were in the order DMA>As(III)>As(V)>MMA. Inorganic As (iAs) accounted for 28% of the As detected. DMA exhibited the highest levels, representing a 72% of total grain As on average.